Understanding Nominal Clauses in English: A Corpus-Based and Pedagogical Perspective - Nathir Ghafar, Zanyar; Anwar, Ary Bahman; Mohamad, Ayad Hamed; Hassan, Jalal Sa'adullha (Universitas Negeri Padang, 2026)
Nominal clauses are a fundamental yet often challenging syntactic category in English grammar, functioning as noun phrases within larger sentence structures. Despite their frequent use in academic, formal, and everyday language, learners of English as a foreign language (EFL) frequently struggle to identify, categorize, and accurately produce nominal clauses. This study presents a comprehensive and theoretically grounded account of nominal clauses, focusing on definitions, formal types, syntactic functions, and pedagogical implications. Drawing upon a wide range of major grammatical theories and corpus-based research, the paper synthesizes traditional and contemporary perspectives on nominal clauses and situates their analysis within broader discussions of clause structure and nominalization. The narrative combines descriptive grammar with analytic frameworks, enhanced with illustrative examples and comparisons to other clause types. The paper concludes with pedagogical recommendations to support learners in mastering nominal clauses and a summary of key findings. This research contributes to both linguistic theory and language teaching by clarifying the nature of nominal clauses and highlighting their significance in advanced English proficiency.